Development of e-learning as a medium of simulation learning and digital communication for vocational school students - Zaudah Cyly Arrum Dalu; Sulistianingsih AS (Jurnal Taman Vokasi, 2019)
The teaching process is a communication process between teachers and students, as wellas a student with other students. Thus, materials or information delivered by the teachers should bewell-accepted by the students and received the right feedbacks. But, when digital simulation andcommunication teaching process was conducted, there were some problems. The problems were time,space/distance, media, limited learning resources which were not able to fulfill the needs of theteaching processes, and also the psychological barriers within the students’ selves. From thoseproblems, an e-learning teaching media was developed based on the needs, characteristics, and stylesof the students as Z generation nowadays. The development of this e-learning media applied stepsfrom Lee Owens model, which are analysis, design, development, implementation, and evaluation.The result of the event then was validated by the material experts, media experts, and the students. Theoverall result showed the media was valid and suitable to use as an alternative for getting the learningresources. The result of the competency test toward students on average achieved 81.7%, whichshowed that there was an increase in learning outcome using e-learning, and it reached the minimumcriteria of completeness